Simple, rapid, and accurate malaria diagnostic platform using microfluidic-based immunoassay of Plasmodium falciparum lactate dehydrogenase - Lee, Wang Sik (Nano Converg, 2020)
This work reports on a rapid diagnostic platform for the detection of Plasmodium falciparum lactate dehydrogenase (PfLDH), a representative malaria biomarker, using a microfluidic microplate-based immunoassay. In this study, the microfluidic microplate made it possible to diagnose PfLDH with a small volume of sample (only 5 μL) and short time (< 90 min) compared to conventional immunoassays such as enzyme-linked immunosorbent assay (ELISA). Moreover, the diagnostic performance of PfLDH showed high sensitivity, specificity, and selectivity (i.e., 0.025 pg/μL in phosphate-buffered saline and 1 pg/μL in human serum). The microfluidic-based microplate sensing platform has the potential to adapt simple, rapid, and accurate diagnoses to the practical detection of malaria.